Patients’ loyalty to primary care institutions and associated factors in China: a cross-sectional study - Liqing Li; Qi Zhang; Liyong Zhu; Guohua Zeng; Hongwei Huang; Zhensheng Chen; Xiaogang Zhou; Xiaofang Wang; Zisheng Xu; Chunmei Wu; Di Yang; Xiaoting Zhai; et al. (BMC Health Services Research)
Abstract Objectives This study aimed to examine patients’ loyalty and explore some associated factors among PCIs in this country. Methods A multistage stratified random sampling method was employed to collect data for this study. A structured self-administered questionnaire was distributed to 2,697 patients who had ever involved in seeking healthcare from PCIs across China between July and September in 2021. The Patients’ Loyalty Scale (PLS) was measured with a 7-item scale. Group differences of PLS scores were estimated by the t-tests or ANOVA analysis. Stepwise regression analysis was used to identify the factors associated with patients’ loyalty to PCIs. Results Based on the PLS with a total score of 35, the average score of patients’ loyalty was 23.81 (SD = 5.42). Multiple linear regression analysis indicated that respondents who were female (β = 0.502), older (β = 0.040), married (β = 0.568), with bachelor degree (β = 0.481), with more than three family members (β = 0.510), employees of enterprises and institutions (β = 1.079), with better self-reported health status (β = 1.938), or a moderate level of self-reported health status (β = 1.510), without a family doctor contract (β = 0.625), with willingness for medical treatment from PCIs (β = 1.172), with higher patients’ trust (β = 0.311) or with higher patients’ satisfaction (β = 0.368) reported a higher level of loyalty. Conclusion Patients’ loyalty among PCIs was found to be above average in China. Gender, age, marital status, education level, occupation, health status, number of family members, family doctor contract, patients’ trust, patients’ satisfaction, and willingness to obtain medical treatment from PCIs were significant predictors of patients’ loyalty.